Application of Folin-Ciocalteau colorimetric method in the determination of total tannin in maize and soybean food products - Adegbusi, H. S.; Ismail, A.; Mohd Esa, N.; Azuan Mat Daud, Z. (Faculty of Food Science & Technology, UPM, 2022)
Yellow maize (Zea mays L.) and soybean (Glycine max (L.) Merr.) are local raw materials used in the formulation of complementary foods in Nigeria. The presence of antinutritional factors such as tannins in them could disrupt the nutritional status in infants and young children, thus leading to malnutrition. However, data on the total tannin contents in maize, soybean, and their products remain limited. This could be due to the lack of a fast, accurate, and inexpensive analytical method for tannin determination. The present work thus evaluated the Folin-Ciocalteu (FC) assay for the accurate quantification of total tannin from yellow maize, soybean, and their products. Techniques including soaking, dehulling, oven-drying, boiling, and frying were used to process the raw materials, prior to grinding and subsequent formulation of their products. The FC method was validated to quantify the total tannin contents from extracts of tested samples by ultraviolet-visible (UV-Vis) spectrophotometry. The original extracts from the tested samples, and external standards from tannic acid and total phenolics (µg/µL) were used for method validation. The method validation showed that the instrumental response to standard tannic acid and the investigated analytes were specific, linear (R2 = 0.998), precise (% CV < 20%), and accurate (recovery = 91%). The limits of detection (LOD) and limits of quantification (LOQ) were 0.03 and 0.09 µg/µL, respectively. The validation complied with the requirements to ensure the reliability of the results. The combined processing techniques were also effective in reducing the total tannin content of maize (0.213 to 0.041% TAE) and soybean (0.257 to 0.064% TAE) by 81 and 75%, respectively. The present work demonstrated the suitability of the FC method as an analytical tool for the quantification of total tannin from plant-based food products.